Product development of a shoe sole - Ng, Tian Jun (Nanyang Technological University, 2022)
Knee Osteoarthritis (OA) is the thinning of the articular cartilage. The articular cartilage is a thin lubricating layer between the bones that form the knee joint, and the thinning of it may lead to pain and disability. OA affects up to 10 percent of the adult and 20 percent of the elderly population in Singapore. As the number of people affected are expected to rise, it is essential to find the optimum method to reduce the progression of knee osteoarthritis. The existing design of various shoes such as lateral wedge insole shoe, variable stiffness intervention shoe, lateral offset shoe sole, barefoot mimicking shoe, and AposHealth physiotherapy shoe which targets knee osteoarthritis was studied. The author concluded that the best way to reduce progression of knee osteoarthritis was to lower the knee adduction moment (KAM) by shifting the centre of pressure (COP) laterally. With exception to the barefoot mimicking shoe, the other designs did not manage to reduce the KAM below that of the barefoot gait. However, it is unclear how a barefoot mimicking footwear managed to reduce the KAM below that of the barefoot gait. As such, the effects of varying flexibility in a shoe sole will be studied in this report. Different infill design was first studied and tested. The main purpose was to determine the best infill design for a flexible shoe sole. In addition, design of experiments (DOE) was conducted to determine the effect of each variable on the flexibility of the design. After the selection of the infill design, it was added onto the shoe sole design that fitted the participant. Finally, biomechanical test was carried out with different shoe sole designs and the KAM and centre of pressure (COP) locations were recorded. The flexible shoe sole design managed to lower the KAM as compared to an existing OA shoe in the market but there is still a slight increase in KAM as compared to the barefoot gait. The results suggest that varying flexibility of a shoe sole does have an effect on the COP location. However, as the test was limited to 1 participant, more tests need to be done with a larger sample size for a definite conclusion.